BAHASA IBU (BAHASA DAERAH) DI PALANGKARAYA: PERGESERAN DAN PEMERTAHANANNYA - R. Hery Budhiono (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
This paper, firstly, aims to find out what language situation happens in Palangkaraya. The second aim is to find out the urgency of language maintenance and the factors affecting people in using their language. The language, mainly, functions as an instrument to communicate. A living language is one that has been being used and maintained by its speakers. Native language or mother tongue is one that is spoken traditionally by a community in a certain region: Javanese language for the Javanese, Sundanese language for the Sundanese, and Ngaju for Dayaks. Language maintenance is an attempt done by the community to maintain its native language. In other words, it denotes the continuing use of a language in the face of competition from a regionally and socially more powerful language. When the maintenance comes to a crash, the language dies slowly. Meanwhile, if it can compete with the other languages, it will survive.